2015
DOI: 10.1017/mag.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

The ‘hitchhiker triangle’ and the problem of perimeter = area

Abstract: In a recent Student's problem in the Gazette, a triangle is formed from three rectangular strips of paper lying on a flat surface. Their widths were given and the challenge was to find the sides of the triangle so formed. These turned out to be in the proportions 7: 15: 20 [1].The triangle with sides , , is a curious one. It has both perimeter and area ( ) equal to 42. In his Hitchhiker's Guide to the Galaxy Douglas Adams thought '42' the 'answer to the ultimate question of life, the universe, and everything' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…We shall use a standard method for considering integer-sided triangles, based upon the incircle, [2].…”
Section: Some Basic Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We shall use a standard method for considering integer-sided triangles, based upon the incircle, [2].…”
Section: Some Basic Resultsmentioning
confidence: 99%
“…A proof of this result was given by Whitworth [1]. Since Whitworth's time, much attention has been given to triangles whose areas are integer multiples of their perimeters, for example [2,3]. However, as this paper will show, Heronian triangles with areas less than their perimeters have some mathematical interest.…”
Section: Stan Dolanmentioning
confidence: 94%
See 1 more Smart Citation
“…In [1], an investigation of integer-sided triangles led to a number of interesting results, including a proof of a proposition equivalent to the result given below. In this Note, the repeated application of an elementary inequality will be used to obtain a simple direct proof.…”
Section: The Diophantine Equation N (X + Y + Z) = Xyzmentioning
confidence: 93%
“…Upper bounds for the solution terms or their sum are needed for computational enumeration. In 2015, Tony Crilly and Colin Fletcher found that the maximum semiperimeter of an integer-sided triangle tightly wrapping a circle of a radius r is (r 2 + 1)(r 2 + 2) [23]. The semiperimeter in their calculation equaled the sum of solution terms of the Diophantine Equation ( 8) with F = r 2 ; thus, they established an upper bound for the sum of solution terms of (8) to be (F + 1)(F + 2).…”
Section: Diophantine Equations Xy = F(x + Y) and Xyz = F(x + Y + Z): ...mentioning
confidence: 99%